Defining body-weight reduction as a humane endpoint: a critical appraisal. (February 2020) - Talbot, Steven R; Biernot, Svenja; Bleich, Andre; van Dijk, Roelof Maarten; Ernst, Lisa; Häger, Christine; Helgers, Simeon Oscar Arnulfo; Koegel, Babette; Koska, Ines; Kuhla, Angela; Miljanovic, Nina; Müller-Graff, Franz-Tassilo; et al.
In many animal experiments scientists and local authorities define a body-weight reduction of 20% or more as severe suffering and thereby as a potential parameter for humane endpoint decisions. In this study, we evaluated distinct animal experiments in multiple research facilities, and assessed whether 20% body-weight reduction is a valid humane endpoint criterion in rodents. In most experiments (restraint stress, distinct models for epilepsy, pancreatic resection, liver resection, caloric restrictive feeding and a mouse model for Dravet syndrome) the animals lost less than 20% of their original body weight. In a glioma model, a fast deterioration in body weight of less than 20% was observed as a reliable predictor for clinical deterioration. In contrast, after induction of chronic diabetes or acute colitis some animals lost more than 20% of their body weight without exhibiting major signs of distress. In these two animal models an exclusive application of the 20% weight loss criterion for euthanasia might therefore result in an unnecessary loss of animals. However, we also confirmed that this criterion can be a valid parameter for defining the humane endpoint in other animal models, especially when it is combined with additional criteria for evaluating distress. In conclusion, our findings strongly suggest that experiment and model specific considerations are necessary for the rational integration of the parameter 'weight loss' in severity assessment schemes and humane endpoint criteria. A flexible implementation tailored to the experiment or intervention by scientists and authorities is therefore highly recommended.